Development of a continuous professional development training module based on multicultural counselling competency for professional counsellors in Malaysia - Aga Mohd Jaladin R.; Amit N.; Anuar A.A.; Fernandez J.A.; Salleh S.; Rais H.; Lim H.S. (SAGE Publications Inc., 2024)
Indexed by WOS/Scopus/ERA